Fungsi Humas sebagai Jabatan Fungsional dalam Meningkatkan Komunikasi Publik di SDN Sempusari 01 Jember - Mufidatul Rosidah; Muhammmad Lutfi Alghifari; Muhammad Qutbir Rabbani; Muhammad Zaki Bahtiar; Rofiq Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Public relations in schools plays a crucial role in building effective communication between the school and the community. Its primary functions include disseminating information, building a positive image, and establishing cooperation with external parties. This study aims to assess the implementation of the Public Relations function as a functional position in improving public communication at SDN Sempusari 01 Jember. The approach used was descriptive qualitative with data collection through interviews, observation, and documentation. The results indicate that although the Public Relations function has been implemented, its implementation is still not optimal. Communication activities such as publications and community engagement have been carried out, but are not well structured. The main obstacle lies in the lack of functional staff and understanding of the role of public relations. Therefore, improving the competence of teaching staff is necessary for a more optimal role of Public Relations in strengthening public communication in elementary schools.